Evaluation of Social and Clinical Factors Associated with Adverse Drug Reactions Among Children with Drug-Resistant Tuberculosis in Pakistan - Said, Muhammad Soaib; Fatima, Razia; Ahmad, Rabbiya; Al Rawi, Mahmood Basil A.; Jan, Faheem; Faisal, Sobia; Khan, Irfanullah; Khan, Amer Hayat (Tropical medicine and infectious disease, 2025)
(1) Background: The occurrence, intensity, and characteristics of adverse drug reactions (ADRs) caused by anti-tuberculosis (TB) drugs have consistently been a subject of worry. There is a lack of published research from Pakistan regarding the negative effects of anti-TB treatment on children, specifically about ADRs. In this study, we aimed to investigate the ADR associated with anti-DR-TB treatment in children. (2) Methods: A prospective longitudinal study was conducted in the multicenter setting of Khyber Pakhtunkhwa, Pakistan. A total of 450 TB children in multicenter hospitals under ATT were assessed for ADRs. Naranjo Causality Assessment and Hartwig’s Severity Assessment Scale were used to evaluate the causality and severity. (3) Results: A total of 300 (66.66%) ADRs were reported in 450 people with DRTB. Anemia was the most frequently observed ADR (37.6%) followed by nausea and vomiting (18.6%). On multivariate analysis, the independent variables that had a statistically significant positive association with ADRs were participants aged, 5–14 years (AOR, 0.3 (0.1–0.5), p ≤ 0.001), normal weight (1.1 (2.0–1.9), p < 0.001), and children having comorbidities (AOR, 0.5 (0.1–0.8), p ≤ 0.001). (4) Conclusions: Our findings advocate for personalized treatment approaches, incorporating nutritional support, comprehensive comorbidity management, and vigilant monitoring to mitigate ADRs and improve treatment outcomes.